Larval Helicoverpa zea Transcriptional, Growth and Behavioral Responses to Nicotine and Nicotiana tabacum - Gog, Linus (Insects, 2014)
The polyphagous feeding habits of the corn earworm, Helicoverpa zea (Boddie), underscore its status as a major agricultural pest with a wide geographic distribution and host plant repertoire. To study the transcriptomic response to toxins in diet, we conducted a microarray analysis of H. zea caterpillars feeding on artificial diet, diet laced with nicotine and Nicotiana tabacum (L.) plants. We supplemented our analysis with growth and aversion bioassays. The transcriptome reflects an abundant expression of proteases, chitin, cytochrome P450 and immune-related genes, many of which are shared between the two experimental treatments. However, the tobacco treatment tended to elicit stronger transcriptional responses than nicotine-laced diet. The salivary factor glucose oxidase, known to suppress nicotine induction in the plant, was upregulated by H. zea in response to tobacco but not to nicotine-laced diet. Reduced caterpillar growth rates accompanied the broad regulation of genes associated with growth, such as juvenile hormone epoxide hydrolase. The differential expression of chemosensory proteins, such as odorant binding-protein-2 precursor, as well as the neurotransmitter nicotinic-acetylcholine-receptor subunit 9, highlights candidate genes regulating aversive behavior towards nicotine. We suggest that an observed coincidental rise in cannibalistic behavior and regulation of proteases and protease inhibitors in H. zea larvae signify a compensatory response to induced plant defenses.